Sistem Informasi Manajemen Inventaris Berbasis Web di SDIT Alam Biruni - Fortuna Alfarisi, Alvin; Agita Rindri, Yang; Josi, Ahmat (Jurnal Inovasi Teknologi Terapan, 2023)
SDIT Alam Biruni is a private elementary school located in Jl. Sisingamangaraja Parit 7, Air Ruai, Pemali, Bangka. In managing item inventory, they are still using spreadsheet software. Also, the process of keeping the records of borrowed items is still done manually by writing them in a record book of borrowed items. The goals of this final project are a) designing and developing a website-based inventory management information system, and b) simplify the registering process of item borrowings at SDIT Alam Biruni. The development process is done by following the Waterfall development model and the design process is done by using use case diagram, activity diagram, and entity relationship diagram. The website-based inventory management information system at SDIT Alam Biruni is developed using CodeIgniter 3 framework, Sublime Text editor, PHP programming language, and MySql Database management system. The testing methods that are used to test the system are: 1) Black Box testing method and 2) user satisfaction survey. The result of this study is a website-based inventory management information system that can simplify the registering process of item borrowings at SDIT Alam Biruni, with 82,6% result of user satisfaction survey.